Are adrenergic α1- antagonists beneficial for the access of retrograde ureteral access sheath or semi-rigid ureteroscope access? A systematic review and meta-analysis - Hu, Qibo; Yuan, Chi; Shen, Sikui; Jian, Zhongyu; Jin, Xi; Ma, Yucheng; Li, Hong; Wang, Kunjie (Frontiers in Surgery, 2023)
Introduction： To evaluate the clinical benefit of preoperative adrenergic α1- antagonist therapy in the management of upper urinary calculi. Materials and Methods: Publications were searched for The Cochrane Central Register of Controlled Trials, EMBASE, and MEDLINE until 1 March 2022 that related to the adrenergic α1- antagonist intake as adjunctive therapy before retrograde surgery. Dichotomous data were reported with risk ratios (RR) with 95% confidence intervals (CIs) and the continuous data were reported with mean difference (MD) with 95% CIs Results: There were nine studies with 867 patients included in this meta-analysis. Preoperative adrenergic α1- antagonists could significantly elevate the compared with the placebo. Higher successful access rate to the stone was found in patients who received preoperative adrenergic α1- antagonists than those who received the placebo (RR 1.24; 95% CI 1.17 to 1.33). Besides, the application of preoperative adrenergic α1- antagonists can also elevate 4th-week stone-free rate (RR 1.20; 95% CI 1.12 to 1.28), decrease postoperative analgesia (RR 0.30;95% CI 0.20 to 0.46) and result in a lower risk of overall complications (RR 0.38; 95% CI 0.24 to 0.61). Conclusions: Preoperative adjunctive adrenergic α1- antagonist therapy is effective and safe in the management of retrograde surgery with a higher successful access rate and lower risk of severe complications.